2014
DOI: 10.1038/gt.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Intracisternal delivery of AAV9 results in oligodendrocyte and motor neuron transduction in the whole central nervous system of cats

Abstract: Systemic and intracerebrospinal fluid delivery of adeno-associated virus serotype 9 (AAV9) has been shown to achieve widespread gene delivery to the central nervous system (CNS). However, after systemic injection, the neurotropism of the vector has been reported to vary according to age at injection, with greater neuronal transduction in newborns and preferential glial cell tropism in adults. This difference has not yet been reported after cerebrospinal fluid (CSF) delivery. The present study analyzed both neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…According to this study, although both administration routes generated similar distribution patterns, intra-CSF injection induced a greater CNS transduction. Furthermore, current research validated these findings in cats after intracisternal delivery [132]. This study showed that AAV9 is able to transduce the majority of MNs in the spinal cord and presents low off-target distribution both in newborn and young cats.…”
Section: Intravascular Versus Intrathecal Administrationsupporting
confidence: 75%
“…According to this study, although both administration routes generated similar distribution patterns, intra-CSF injection induced a greater CNS transduction. Furthermore, current research validated these findings in cats after intracisternal delivery [132]. This study showed that AAV9 is able to transduce the majority of MNs in the spinal cord and presents low off-target distribution both in newborn and young cats.…”
Section: Intravascular Versus Intrathecal Administrationsupporting
confidence: 75%
“…There is considerable variability in the literature regarding the main CNS cell type targeted by AAV9. Several factors have been held accountable for the differences observed, including the route of delivery (73,74), the age at administration (75), the animal species (73,(76)(77)(78), the doses used, the promoter included in the expression cassette (74,79), and even the single-or double-stranded nature of the AAV (80). Alternatively, the quality of vector preparations could play an important role in determining vector tropism (81).…”
Section: Discussionmentioning
confidence: 99%
“…However, rAAV2 shows poor transduction efficiency compared with other rAAVs. Recently, it has been shown that rAAV8 and 9 are more efficiently transduced into CNS lesions after IT or IV administration [51,64,66,7175]. In this section, we summarized recent studies of rAAV-mediated gene therapy in animal models of each type of MPS.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%